2020
DOI: 10.3390/ani10101724
|View full text |Cite
|
Sign up to set email alerts
|

Mannanoligosaccharides as a Carbon Source in Biofloc Boost Dietary Plant Protein and Water Quality, Growth, Immunity and Aeromonas hydrophila Resistance in Nile Tilapia (Oreochromis niloticus)

Abstract: The aim of the present study was to evaluate mannan oligosaccharides (MOS) or glycerol (GLY) as a carbon source on biofloc systems of Nile tilapia (O. niloticus) juveniles. Fish (n = 750) were reared in open flow (Controls) or biofloc systems (B-GLY and B-MOS) fed with a plant or fish protein source over a period of twelve weeks. Total ammonia nitrogen and nitrate decreased in the biofloc groups, while biofloc volume increased in B-MOS. Compared to the controls, B-MOS and B-GLY exhibited higher weight gain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 81 publications
(91 reference statements)
5
29
0
Order By: Relevance
“…In this study, total presumptive Vibrio, total coliform and Aeromonas count were significantly lower in BFT water and fish gut compared with CWS at the end of study. These results were coherent with previous findings (Kishawy et al., 2020; Kumar et al., 2018; Luis‐Villasenor et al., 2015; Martins et al., 2020; Panigrahi., 2017, 2018, 2019). Water samples collected from White leg shrimp and Nile tilapia culture tanks, a sugar cane‐based biofloc system, showed lower relative abundance of vibrionacea using next‐generation sequencing (Martins et al., 2020).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, total presumptive Vibrio, total coliform and Aeromonas count were significantly lower in BFT water and fish gut compared with CWS at the end of study. These results were coherent with previous findings (Kishawy et al., 2020; Kumar et al., 2018; Luis‐Villasenor et al., 2015; Martins et al., 2020; Panigrahi., 2017, 2018, 2019). Water samples collected from White leg shrimp and Nile tilapia culture tanks, a sugar cane‐based biofloc system, showed lower relative abundance of vibrionacea using next‐generation sequencing (Martins et al., 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Similar growth pattern was observed in Nile tilapia reared in BFT by Kishavy et al. (2020). Besides this, weight gain and FCR of the present study were found to be better than the Durigon et al.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The overall results provide impressive outcomes regarding using Y. schidigera in terms of potential interest in open-flow pond aquaculture and closed aquaculture systems. Correspondingly, Y. schidigera can be complementary to biofloc technology, which can also improve the growth and immune status of farmed fish via improving water quality parameters [ 96 ].…”
Section: Yucca As a Natural Cleaner For Aquatic Water Qualitymentioning
confidence: 99%